National Recovery and Resilience Plan: Portugal - Ana Teresa Ribeiro (Italian Labour Law e-Journal, 2022)
This article addresses not only Portugal’s position vis-à-vis the NGEU, but also the contents of the national Recovery and Resilience Plan and its assessment by the European Commission and the Council. It provides an overview of its most significant measures with regard to social and employment policies, as well as the plan’s stance regarding the European Pillar of Social Rights, the 2019, 2020, and 2022 Country-Specific Recommendations. The European Commission’s in-depth analysis of Portugal is also examined.